First tomographic observations of gravity waves by the infrared limb imager GLORIA - Krisch, Isabell; Preusse, Peter; Ungermann, Jörn; Dörnbrack, Andreas; Eckermann, Stephen D.; Ern, Manfred; Friedl-Vallon, Felix; Kaufmann, Martin; Oelhaf, Hermann; Rapp, Markus; Strube, Cornelia; Riese, Martin (Copernicus Publications, 2017)
Atmospheric gravity waves are a major cause of uncertainty in global atmospheric models. This uncertainty affects regional climate projections and seasonal weather predictions. Improving the representation of gravity waves in global atmospheric models, is therefore of primary interest. In this regard, measurements providing an accurate 3-D characterization of gravity waves are needed. Using the Gimballed Limb Observer for Radiance Imaging of the Atmosphere (GLORIA), the first airborne implementation of a novel infrared limb imaging technique, a gravity wave event over Iceland was measured. An air volume disturbed by this gravity wave, was investigated from different angles by encircling the volume with a closed flight pattern. Using a tomographic retrieval approach the measurements of this air mass under different angles allowed for a 3-D reconstruction of the temperature and trace gas structure.